Chronic Anxiety- and Depression-Like Behaviors Are Associated With Glial-Driven Pathology Following Repeated Blast Induced Neurotrauma - Dickerson, Michelle R.; Murphy, Susan F.; Urban, Michael J.; White, Zakar; VandeVord, Pamela J. (Frontiers in Behavioral Neuroscience, 2021)
Chronic Anxiety- and Depression-Like Behaviors are Associated with Glial-Driven Pathology Following Repeated Blast Induced Neurotrauma